The different impact of stimulation duration on oocyte maturation and pregnancy outcome in fresh cycles with GnRH antagonist protocol in poor responders and normal responders - Yu-Chieh Yang; Yi-Ping Li; Song-Po Pan; Kuang-Han Chao; Chin-Hao Chang; Jehn-Hsiahn Yang; Shee-Uan Chen (Elsevier, 2019)
Objective: To study the impact of stimulation duration on intracytoplasmic sperm injection (ICSI) - embryo transfer (ET) outcome in poor and normal responders during controlled ovarian stimulation using gonadotropin-releasing hormone (GnRH) antagonist protocol. Materials and methods: This is a retrospective cohort study. There were 1481 women undergoing ICSI-ET cycles. Women with ovum pick-up number ≤3 were defined as poor responders (n = 235), and those with a number ≥4 were normal responders (n = 1246). Results: The mean stimulation duration was shorter in poor responders with pregnancy group as compared with normal responders with pregnancy group (7.8 ± 2.2 vs. 9.2 ± 1.6 days, p < 0.01). Poor responders with a shortest stimulation duration (≤6 days) appeared a higher live birth rate (≤6 days: 33.3%, 7-8 days: 20.0%, 9-10 days: 15.9%, and ≥11 days: 11.1%, p = 0.18). Normal responders with a shortest stimulation duration (≤6 days) appeared a lowest live birth rate (≤6 days: 28.6%, 7-8 days: 35.8%, 9-10 days: 33.6%, and ≥11 days: 29.3%, p = 0.61). Oocyte maturation rate was significantly lower at stimulation durations ≤6 days group (≤6 days: 67%, 7-8 days: 80%, 9-10 days: 85%, and ≥11 days: 87%, p = 0.02) in normal responders. Conclusion: In ICSI-ET cycles, stimulation duration appears to have different impact on oocyte maturation, clinical pregnancy rates and live birth rates in both poor and normal responders. Keywords: GnRH antagonist, Controlled ovarian stimulation, Poor responder, Normal responder, Stimulation duration